Pengaruh Teknik Relaksasi Nafas dalam terhadap Tekanan Darah pada Penderita Hipertensi di Puskesmas Industri - Risma Fajrina Summasalisa; Widiharti Widiharti; Wiwik Widiyawati (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
The prevalence of hypertension in Indonesia has increased, in 2013 the prevalence of hypertension was 25.8% while in 2018 the prevalence of hypertension increased by 34.1%. In addition to pharmacological techniques, hypertension management can use non-pharmacological techniques, one of which is deep breathing relaxation techniques. The purpose of this study was to analyze the effect of deep breathing relaxation techniques on blood pressure in hypertension patients at the Industrial Health Center. This study used the Pre-Experiment one group pretest and posttest method. The sampling technique was random sampling with a sample size of 46 people who met the inclusion criteria. The instruments used were digital tension, SOP for deep breathing relaxation techniques, and observation sheets. Data analysis used the Wilcoxon statistical test. Blood pressure before the relaxation technique averaged systolic 157.83. Blood pressure after the relaxation technique averaged systolic 137.65. The results of the Wilcoxon blood pressure test in hypertension patients before and after deep breathing relaxation techniques (p = 0.000). There is an effect of deep breathing relaxation techniques on blood pressure in hypertension patients at the Industrial Health Center.